Land Tenure of the Malay People in North Sumatera: From Normative Trap to the Historical Denial - Edy Ikhsan (Faculty of Law, Hasanuddin University, 2016)
The following brief analysis is trying to look at the shifting mechanism of land rights of the Malay people from a historical perspective. The point of analysis stems from the description contained in the literature of customary laws produced by some academics and of the Dutch colonial officials. It subsequently runs using of some secondary materials and other colonial-based archives. The analysis finally concludes that in the span of nearly a half of a century, since the period of the Dutch, Japanese capitulation, the period of independence, the land rights of the Malay people has become a “toy play” of the ruling regimes, with all formulas being implemented in each period. The laws imposed upon this well-known fertile land have been successfully enriching the rulers and a wide range of business people with strong access to it.